Implementasi pop up book dengan konten profil pelajar pancasila untuk meningkatkan konsep berkebhinekaan global pada peserta didik - Margaretha Intan Permatasari; Hasan Mahfud; Septi Yulisetiani (Universitas Sebelas Maret, 2023)
Researchers used pop up books with profil pelajar pancasila to help students better understand the concept of berkebhinekaan global. This study is qualitative and uses the classroom action research approach. Data collection techniques include observation, tests, and documentation. Data validity testing techniques include content validity, triangulation of techniques, and sources. Data analysis is descriptive comparative by comparing the values of the pre-action test results of cycle 1, 2, and 3. Researchers also use interactive data analysis, which consists of collecting data, reducing data, presenting data, and verifying data. The results of the pre-action test showed a completeness of 7.14% of 2 students with a mean of 47.14. Then, in cycle one there was an increase in completeness of 39.29%, 11 students with a mean of 63.28. In the second cycle the completeness was 75%, a total of 21 students with a mean of 77.28. In the third cycle, the completeness was 89.29%, a total of 25 students with a mean of 80. According to the research that has been done, the use of pop up books with profil pelajar pancasila material in grade 4 SDN Setono, Surakarta in 2022/2023 can enhance comprehension of the concept of berkebhinekaan global.